KARAKTERISTIK WIRAUSAHA DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA TOKO KELONTONG DI KABUPATEN KEBUMEN APAKAH BERPENGARUH? - Rico Edy Purwanto; Jonet Aryanto; Salman Alfarisy Totalia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to determine the influence of entrepreneurial characteristics on business success and entrepreneurial orientation on business success at grocery stores in Kebumen Regency. The research method used is a quantitative descriptive method and data collection techniques using questionnaires. The sampling technique uses a probability sampling technique, namely proportionate random sampling from a population of 11,677 grocery stores with a sample of 117 grocery stores in Kebumen Regency. The research results show that (1) there is a positive and significant influence between entrepreneurial characteristics on business success in the grocery store business in Kebumen Regency with a calculated t value > t table (2.153 > 1.981) a significance figure of 0.033 < 0.05, (2) there is positive and significant influence between entrepreneurial orientation on business success in grocery store businesses in Kebumen Regency with a calculated t value > t table (5.542 > 1.981) and a significance figure of 0.000 < 0.05, (3) there is a simultaneous influence between entrepreneurial characteristics and entrepreneurial orientation towards business success in the grocery store business in Kebumen Regency with a calculated F value > F table (56.762 > 3.080).